Selecting public goods institutions: Who likes to punish and reward? - Michalis Drouvelis; Julian C. Jamison (Federal Reserve Bank of Boston, 2012)
The authors extend the standard public goods game in a variety of ways, in particular by allowing for endogenous preference over institutions and by studying the relationship between individual types, their preferences, and later behavior within the various institutional environments. They collect individual data on a variety of demographic factors, in addition to measuring levels of risk aversion and ambiguity aversion (over both gains and losses). The authors then elicit preferences in an incentive-compatible manner over voluntary contribution mechanisms with and without reward and punishment options. Finally, they randomly assign subjects to one of the four institutions and observe repeated play. They find that payoffs are significantly greater when punishment is allowed but that only a small minority of participants prefers such an environment. There is at most a weak link between individual characteristics and elicited preferences over environments. On the other hand, institutional preferences, as well as individual characteristics, are more strongly predictive of behavior in the public goods game. For instance, loss averse individuals preemptively reward more often when that option is available. This result suggests that when studying social interactions, especially if people can choose whether to participate in a sanctions-and-rewards mechanism, it is important to consider individual attitudes toward risk and uncertainty.
Keywords: C92; H41; D81; 330; public goods; voluntary contribution; risk; loss; and ambiguity aversion; preference elicitation; reward and punishment